The Effect of Green Investment on the Disclosure of Carbon Emissions from SRI-Kehati Companies - Vianney Parameswara Ali; Luky Patricia Widianingsih (Jurnal Ekuilnomi, 2025)
This study examines how green investment affects carbon emission disclosure in companies listed on the SRI-Kehati index. Using the PROPER rating as a proxy for green investment, this research applies a quantitative approach with multiple linear regression analysis on data from 25 companies. The Carbon Emission Disclosure Index (CED) measures transparency in emissions reporting, with firm size as a control variable. The findings reveal a positive relationship between green investment and carbon emission disclosure. Companies with higher PROPER ratings tend to be more transparent in reporting their carbon emissions. This confirms that sustainable investment enhances corporate environmental accountability. The study’s implications suggest that PROPER ratings can serve as a benchmark for improving carbon disclosure standards. Therefore, policymakers and regulators should encourage businesses to invest in environmentally friendly practices to enhance transparency and support climate change mitigation efforts